Program “CERDIK” Meningkatkan Perilaku Pencegahan Hipertensi Pada Penderita Usia 45-54 Tahun - Adzkia Zahra Kamila; Andra Vidyarini; Mohammad Furqan (Poltekkes Kemenkes Semarang, 2024)
Background: In Indonesia, there is an increasing prevalence of hypertension in the 45-54 age group. This degenerative disease has a significant impact with high morbidity and mortality rates, and affects the quality of life of sufferers. Hypertension can increase the risk of developing cardiovascular disease, coronary heart disease, stroke, kidney damage and diabetes mellitus. The